E-SECURITY AND E-TRUST ON REPURCHASE INTENTION THROUGH E-SATISFACTION OF SHOPEE CONSUMERS IN PALU CITY - Karim, Dhifa Latifah; Wahyuningsih; Muzakir (Master of Management Study Program, Faculty of Economics and Business, Tadulako University, 2024)
This study aims to determine and analyze the effect of e-security and e-trust on repurchase intention with e-satisfaction as an intervening variable for Shopee consumers in Palu City. This type of research is descriptive, in that it seeks to evaluate and analyze the effect of the independent variable on the dependent variable. The sample of this study consisted of users of Shopee's online buying and selling service who had made more than one purchase in Palu City. This was determined using a purposive sampling method and amounted to 120 people. This study uses the Partial Least Squares (PLS) analysis method using the SmartPLS application. The results of this study indicate that 1) E-security does not have a positive and significant effect on e-satisfaction for Shopee consumers in Palu City. 2) E-Trust positively and significantly affects e-satisfaction for Shopee consumers in Palu City. 3) E-Security has no positive and significant effect on repurchase intention for Shopee consumers in Palu City. 4) E-Trust has a positive and significant effect on repurchase intention for Shopee consumers in Palu City. 5) E-satisfaction has a positive and significant effect on repurchase intention for Shopee consumers in Palu City. 6) E-security has a positive and significant effect on repurchase intention through e-satisfaction for Shopee consumers in Palu City. 7) E-Trust positively and significantly affects repurchase intention through e-satisfaction for Shopee consumers in Palu City.